Timber Volume Estimation Model for Commercial Tree Species in the Logging Area Concession of PT. Tunas Timber Lestari in Boven Digul, Papua - Freddy Jontara Hutapea; Relawan Kuswandi (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2019)
The volume estimation model is one of the most important components in developing sustainable forest management. Nowadays, various models for various types of forests in Indonesia have developed. Nevertheless, these models do not represent the type of forest ecosystem in Papua. Therefore, numerous studies are still needed to develop volume estimation model for various types of forests in Papua. This study was aimed to develop timber volume estimation model for commercial tree species in logging concession of PT. Tunas Timber Lestari in Sesnukt District, Boven Digul Regency, Papua Province. A total of 164 trees were chosen to develop the model and 50 trees for model validation. The result showed that diameter did not have a strong correlation with tree height. Therefore, the model should be developed using the combination of diameter and tree height. The best model in the development stage was selected based on the value of coefficient of determination (R2), standard error of the estimate (SEE), and Ftest. The best model in the validation stage was selected based on the value of bias (e), root mean square errors (RMSE), average deviation (SR), aggregative deviation (SA), and χ2test.. The best model for timber volume estimation in PT. Tunas Timber Lestari are V = 0.00007594 D1.978 H0.923. Keywords: commercial tree species, diameter, timber volume estimation, tree height, volume